Uncovering nitroxoline activity spectrum, mode of action and resistance across Gram-negative bacteria - Elisabetta Cacace; Manuela Tietgen; Meike Steinhauer; André Mateus; Tilman G. Schultze; Marina Eckermann; Marco Galardini; Vallo Varik; Alexandra Koumoutsi; Jordan J. Parzeller; Federico Corona; Askarbek Orakov; et al. (Nature Communications)
Abstract Nitroxoline is a bacteriostatic quinoline antibiotic, known to form complexes with metals. Its clinical indications are limited to uncomplicated urinary tract infections, with a susceptibility breakpoint only available for Escherichia coli. Here, we test > 1000 clinical isolates and demonstrate a much broader activity spectrum and species-specific bactericidal activity, including Gram-negative bacteria for which therapeutic options are limited due to multidrug resistance. By combining genetic and proteomic approaches with direct measurement of intracellular metals, we show that nitroxoline acts as a metallophore, inducing copper and zinc intoxication in bacterial cells. The compound displays additional effects on bacterial physiology, including alteration of outer membrane integrity, which underpins nitroxoline’s synergies with large-scaffold antibiotics and resensitization of colistin-resistant Enterobacteriaceae in vitro and in vivo. Furthermore, we identify conserved resistance mechanisms across bacterial species, often leading to nitroxoline efflux.